2001
DOI: 10.1038/sj.onc.1204846
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of chromosome 3p deletion on the expression of the putative tumor suppressor RARβ and on retinoid resistance in human squamous carcinoma cells

Abstract: Retinoids' eects on cell growth and dierentiation are mediated by nuclear retinoid receptors, which are ligandactivated transcription enhancing factors. Because the expression of the retinoic acid receptor b (RARb) gene, which is located on chromosome 3p24, is diminished in premalignant and malignant tissues it has been proposed that it acts as a tumor suppressor. To test the hypothesis that RARb loss leads to retinoid resistance, we studied several karyotyped head and neck squamous carcinoma (HNSCC) cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
(49 reference statements)
2
20
0
Order By: Relevance
“…On the other hand, similar treatment of cell lines that exhib- ited basal expression of TIG1 resulted in a significant induction of expression. In a previous study (22), we observed the same pattern in the inducibility of RAR␤2 expression, which occurred only in cell lines that had at least some basal endogenous expression of RAR␤2. These data suggest that individual cell lines with a minimum endogenous level of TIG1 expression exhibit an increase in expression after retinoic acid treatment.…”
Section: Discussionmentioning
confidence: 68%
“…On the other hand, similar treatment of cell lines that exhib- ited basal expression of TIG1 resulted in a significant induction of expression. In a previous study (22), we observed the same pattern in the inducibility of RAR␤2 expression, which occurred only in cell lines that had at least some basal endogenous expression of RAR␤2. These data suggest that individual cell lines with a minimum endogenous level of TIG1 expression exhibit an increase in expression after retinoic acid treatment.…”
Section: Discussionmentioning
confidence: 68%
“…The protective effect exerted by retinol and α-tocopherol could be explained by their role as potent regulators of cellular activities, thus having significant impact on oral carcinogenesis (Mukherjee et al, 2011). These micronutrients are also strong antioxidants that have been shown to suppress the development of malignancy in cell culture experiments and animal studies (Zou et al, 2001). Although the mechanism of action is rather complex and unclear, it has been hypothesized that antioxidant activity of these micronutrients prevents tissue damage by deactivating excited oxygen molecules and neutralizing free radicals (Poljsak, 2007) which then translates into the protective effects seen.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Although several genes, for example, p14, p15, p16, RASSF1A, VHL, hMLH1, and MGMT, have been reported to be silenced by aberrant DNA methylation, (9)(10)(11)(12)(13)(14)(15)(16) some of them were infrequently methylated in OSCC compared with other tumors. In order to create the b.est possible panel of markers for the prediction of outcome, sensitivity to chemotherapy and radiation, and disease status OSCC, more candidates for tumor-suppressor genes targeted by promoter methylation will no doubt be tested in this disease.…”
mentioning
confidence: 99%